Development of Hypoglycemia Management Scale for Teachers of the Children with Type 1 Diabetes. - ÇÖVENER ÖZÇELİK, ÇAĞRI (My University, 2024)
Objective: Hypoglycemia which is an acute complication of diabetes is an absolutely serious and may possibly develop at any moment. Each of the schools do not have a nurse to intervene in emergency. Thus, the responsibility for such emergency situations put on the shoulders of teachers. The objective of this research was to develop and test the psychometric properties of Hypoglycaemia Management Scale for Teachers. Methods: It was a scale development study with a methodological design. 400 teachers of primary, secondary and high schools were included in the study. The item pool was 30. The scale was presented to 5 of the experts and after the content validity the draft scale was 31 items. Data collected between the dates 6th Feb to 11th March 2020. Teachers filled the data collection tools by themselves. Factor analyses, item-total correlation, split-half reliability, test-retest reliability was tested for psychometric properties. Results: The scale had 11 items and 2 subscales named “Hypoglycemia Knowledge” included some hypoglycemia-related expressions and “Hypoglycemia Management” included some expressions related with the practices to be followed in hypoglycemia situations. Conclusion: A reliable and valid scale was developed to measure hypoglycemia management of teachers. It may be used in practice to assess hypoglycemia management of teachers in school setting. Keywords: Scale development, hypoglycemia management, teacher, school, type 1 diabetes.
Keywords: Hemşirelik; Çocuk Sağlığı ve Hastalıkları Hemşireliği; Sağlık Bilimleri; Nursing; Child Health and Diseases Nursing; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Scale development; hypoglycemia management; teacher; school; type 1 diabetes